CARDIORESPIRATORY RESPONSES TO ISOKINETIC EXERCISE IN PATIENTS WITH CORONARY ARTERY DISEASE - Ribeiro,Aline Ertel (2020)
ABSTRACT Introduction Exercise training using an isokinetic dynamometer is an alternative for improving muscle strength in patients with coronary artery disease (CAD). Few studies have shown metabolic and cardiorespiratory responses to submaximal isokinetic exercises in patients in cardiac rehabilitation programs. Objective To describe cardiorespiratory responses at two intensities of isokinetic exercise. Additionally, we compared the cardiorespiratory responses of isokinetic exercise with data from the incremental cardiopulmonary exercise test (CPET). Methods Eight individuals with CAD (61.7 ± 6.6 years) performed the following tests: 1) CPET on a treadmill; 2) Peak torque test (five repetitions) and fatigue resistance test (20 repetitions) of knee flexion-extension at angular speeds of 120°/s and 180°/s; 3) Two sets of 20 repetitions were performed at 30–40% (low-intensity, LI) and 50–60% (moderate-intensity, MI) of peak torque at angular speeds of 120°/s and 180°/s, using an isokinetic dynamometer. During the exercises, the individuals were connected to an expired gases analyzer with simultaneous monitoring of the electrocardiogram trace, heart rate (HR), oxygen consumption (VO2), carbon dioxide production, and minute ventilation (VE). The differences (∆) between the peak measurements during exercises and the baseline values were calculated. Results Both LI and MI produced cardiorespiratory responses below the anaerobic threshold (82.8 ± 8.1% of HRmax and 74.4 ± 9.6% of VO2peak) compared to the CPET data ( P < 0.01). MI showed higher ∆ HR (9.8 ± 5.5 vs. 6.3 ± 4.6 bpm; P = 0.01), ∆ rate pressure product (3015 ± 2286 vs. 1957 ± 1932 mmHg·bpm; P = 0.01), and ∆VE (10.2 ± 6.2 vs. 6.9 ± 7 L·min-1; P = 0.03) than LI at the angular velocity of 180°/s. Conclusion These results suggest that this isokinetic exercise protocol may be used as a strategy for cardiac rehabilitation programs in patients with CAD. Level of evidence IV; Case series.